1984
DOI: 10.1177/089686088400400206
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Ambulatory Peritoneal Dialysis in South Africa -A Four-Year Experience

Abstract: This study describes our experience with continuous ambulatory peritoneal dialysis (CAPD) over a four year period, during which 88 patients were offered CAPD. It compares and contrasts the response to CAPD among four racial groups in Natal viz asiatics, blacks, coloureds and whites. Peritonitis -the major complication, occurred with an overall incidence of one episode every 4.41 patient months. CAPD remains a useful alternative therapy in developing countries where a high percentage of patients with chronic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Between 1979 and 1983 the incidence of peritonitis was 2.72 episodes per patient year (2). Since then the incidence has ranged between 2.09 in 1985 and 3.1 episodes in 1987 and 1988 (Tab.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Between 1979 and 1983 the incidence of peritonitis was 2.72 episodes per patient year (2). Since then the incidence has ranged between 2.09 in 1985 and 3.1 episodes in 1987 and 1988 (Tab.…”
Section: Resultsmentioning
confidence: 97%
“…The vast majority of our population in Natal are blacks, most of whom reside either in a rural environment or in peri-urban areas lacking basic ablution and sanitary facilities. For this reason our initial experience with CAPO in these patients was poor (2). We therefore realised that we had to include an "acceptable" socio-economic status to the list of other desirable attributes for CAPO to be a success, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is not always a feasible option, leaving patients to depend on HD and CAPD despite both treatments being costly. CAPD is associated with advantages like better nutritional status, freedom of mobility, control of blood pressure and fluids and better rehabilitation (Naicker 2003;Parsoo et al 1984). In a quantitative study Lok (1996) concluded that CAPD patients experience a higher quality of life than HD patients.…”
Section: Dialysis Optionsmentioning
confidence: 99%